Ultra‐High Performance Amorphous Ga2O3 Photodetector Arrays for Solar‐Blind Imaging - Qin, Yuan; Li, Li‐Heng; Yu, Zhaoan; Wu, Feihong; Dong, Danian; Guo, Wei; Zhang, Zhongfang; Yuan, Jun‐Hui; Xue, Kan‐Hao; Miao, Xiangshui; Long, Shibing (Advanced science, 2021)
The growing demand for scalable solar‐blind image sensors with remarkable photosensitive properties has stimulated the research on more advanced solar‐blind photodetector (SBPD) arrays. In this work, the authors demonstrate ultrahigh‐performance metal‐semiconductor‐metal (MSM) SBPDs based on amorphous (a‐) Ga2O3 via a post‐annealing process. The post‐annealed MSM a‐Ga2O3 SBPDs exhibit superhigh sensitivity of 733 A/W and high response speed of 18 ms, giving a high gain‐bandwidth product over 104 at 5 V. The SBPDs also show ultrahigh photo‐to‐dark current ratio of 3.9 × 107. Additionally, the PDs demonstrate super‐high specific detectivity of 3.9 × 1016 Jones owing to the extremely low noise down to 3.5 fW Hz−1/2, suggesting high signal‐to‐noise ratio. Underlying mechanism for such superior photoelectric properties is revealed by Kelvin probe force microscopy and first principles calculation. Furthermore, for the first time, a large‐scale, high‐uniformity 32 × 32 image sensor array based on the post‐annealed a‐Ga2O3 SBPDs is fabricated. Clear image of target object with high contrast can be obtained thanks to the high sensitivity and uniformity of the array. These results demonstrate the feasibility and practicality of the Ga2O3 PDs for applications in solar‐blind imaging, environmental monitoring, artificial intelligence and machine vision. Ultraviolet imaging technology is widely used in meteorology, medical science, and military science. For the first time, a high‐uniformity 32 × 32 solar‐blind image sensor array with outstanding imaging capability is demonstrated based on high‐performance Ga2O3 photodetectors. Schottky barrier lowering effect is experimentally revealed to attribute to the internal gain mechanism.